Formation of a fibrin based gelatinous coat over repairing rat gastric epithelium after acute ethanol damage: interaction with adherent mucus. Issue 7 (July 1987) - Sellers, L A; Allen, A; Bennett, M K
Abstract : A gelatinous coat, heterogeneous in appearance, was formed over damaged rat gastric mucosa recovering from acute ethanol injury. This coat, in places 1.6 mm thick (median thickness 680 microns), was 10 times thicker than the translucent layer of adherent mucus (median thickness 70 microns) covering the undamaged mucosa. Immunohistochemistry and periodic acid Schiff staining showed this gelatinous coat to be predominantly a fibrin gel with an exterior layer rich in mucus and necrotic cells. The plasma clotting time was significantly decreased in vitro by pig gastric mucus gel and soluble mucus glycoprotein (90% and 13% respectively) suggesting that in vivo the mucus layer remaining after epithelial damage could act as a template for fibrinogen-fibrin conversion. These results show that a fibrin based gelatinous coat, quite distinct from the adherent mucus layer and with considerable protective potential could be formed over the repairing rat gastric mucosa after acute ethanol damage.